Synthesis and Characterization of Novel Phthalocyanines with Four 17-Membered Diazadithiamonooxa MacrocyclesA - Sesalan, Fehmi Ufuk; Okur, Ali Ihsan (Informa UK Limited, 1999)
Abstract New phthalocyanines, (M = Cu, Zn, Ni) substituted with four 17-membered N2S2O macrocycles have been prepared starting from 1, 5-bis(2′-aminophenylthia)-3-oxapentane (la), which was tosylated and then subsequently reacted with 1, 2-dibromo-4, 5-bis(bromomethyl)benzene to form the macrocyclic structure (2a). The phthalocyanines (3) - (5) are soluble in chloroform, DMF, DMSO and pyridine.